Programa educativo de real - life drama para mejorar la comunicación oral en inglés en estudiantes de segundo grado de secundaria en la Institución Educativa Alexander Von Humboldt de Punchana 2023 - Huesember Viena, Telassim Isabel (2025)
The objective of this research was to evaluate the effect of the Real Life Drama educational program on improving oral communication in English among second grade high school students at Alexander Von Humboldt Educational Institution in the Punchana district in 2023. The current study employed a quantitative nature, adopting a field, contemporary, univariable, and quasi-experimental design with pre test and post-test. The population consisted of 85 students with a sample of 57 students divided into two groups, experimental and control. Three tests were utilized: an oral comprehension test, an oral performance test, and a rubric for data collection. Following the tests, the results showed that the experimental group demonstrated a significant increase in their average compared to the control group on a scale of 0-20 (13.006 > 11.240). In conclusion, the application of the program employing the real-life drama strategy significantly improved oral communication, along with its dimensions such as information retrieval, inference and interpretation, oral comprehension, strategic interaction, use of non-verbal and paraverbal resources, and oral performance in English, among the two study groups. This result is supported by a p-value lower than (α = 0.05), which was the established significance level.